2022
DOI: 10.1177/10820132221096995
|View full text |Cite
|
Sign up to set email alerts
|

The spatial distribution and migration of three typical fungicides in postharvest satsuma mandarin (Citrus unshiu Marc.) fruit

Abstract: Fungicides are often used to extend the storage time of postharvest satsuma mandarin fruit. In recent years, fungicide residue has become an issue of food safety. This study aimed to investigate the distribution and migration of three typical fungicides (imazalil, prochloraz, thiophanate-methyl) in postharvest satsuma mandarins using liquid chromatography-tandem mass spectrometry (LC-MS/MS). Three fungicides could quickly penetrate satsuma mandarins and their gradient concentrations of residues in the fruit we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Penicillium italicum is one of the main pathogens causing citrus blue mold, which results in significant economic losses during the transportation and storage of citrus fruits after harvest 10 . Prochloraz, imazalil, and mildothane are typical fungicides for the prevention and control of citrus blue mold, but their extensive use has raised increasing worries about pesticide residues, food safety, and the development of fungicide‐resistant P. italicum mutants 11 . Therefore, there is an urgent need to develop novel and safe antifungal agents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Penicillium italicum is one of the main pathogens causing citrus blue mold, which results in significant economic losses during the transportation and storage of citrus fruits after harvest 10 . Prochloraz, imazalil, and mildothane are typical fungicides for the prevention and control of citrus blue mold, but their extensive use has raised increasing worries about pesticide residues, food safety, and the development of fungicide‐resistant P. italicum mutants 11 . Therefore, there is an urgent need to develop novel and safe antifungal agents.…”
Section: Introductionmentioning
confidence: 99%
“…10 Prochloraz, imazalil, and mildothane are typical fungicides for the prevention and control of citrus blue mold, but their extensive use has raised increasing worries about pesticide residues, food safety, and the development of fungicide-resistant P. italicum mutants. 11 Therefore, there is an urgent need to develop novel and safe antifungal agents. It has been reported that the citrus blue mold can be effectively controlled by some plant essential oils and microbial extracts, which have the potential as alternatives to conventional chemical synthetic fungicides.…”
Section: Introductionmentioning
confidence: 99%